Quality of life in the elderly: A community study - Emitis Jazayeri; Shahla Kazemipour; Seyed Reza Hosseini; Majid Radfar (Babol University of Medical Sciences, 2023)
Background: Standard information about the physical, mental, and social status of older people is needed to promote their health. The aim of this study was to determine the physical, mental and social health status of older people in Mazandaran, taking into account the specific climatic conditions and public culture, and to adapt it to the indicators of the "Aging and Health Program" of the World Health Organization (WHO) to localize and better use this index. Methods: In this cross-sectional study, 390 elderly aged ≥65 years in Mazandaran were selected by the quota method. Their physical, mental, and social health status and demographic information were collected using a questionnaire (a 36-item short-form health survey (SF-36)) and face-to-face interviews. Physical and mental health status was classified into five levels based on the score obtained. The data were analyzed using SPSS 26. Results: The average age of the elderly was 71.48 years. In terms of physical performance, 40.7% of the elderly were below and 30.8% above the average of international standards. In terms of mental health, 18.9 and 41.5% of the elderly were below and above the average, respectively, and 17 and 51.8% of the elderly had low and high social performance, respectively. The Pearson correlation test showed a significant relationship between physical health (0.176), mental health (0.16), and social health (0.178) and quality of life at the 0.01 level. Conclusion: The physical, mental and social health status of the elderly in Mazandaran is far from the indicators of health in old age established by WHO, and their condition is unfavorable (at least in terms of physical and mental health).